Yoga e atenção: os efeitos da prática de yoga em crianças pré-escolares com traços importantes de problemas atencionais - Neuman, Marcella Barbosa (2015)
It´s expected that at pre-school age the attention is still in training. Nevertheless, the complaints about attention behavior in this age group have been justifying new studies on interventions which may minimize the damages from such patterns, mainly in the educational arena. Despite the growth in the literature suggesting new studies about pre-schoolers and attention this still being poorly documented. This study aimed to observe the effects of a psychosomatic practice as yoga can have in behavior attention and external problems shown in the educational arena in such age group. This randomized clinical trial deals with the development, implementation and evaluation of a yoga practice protocol of 11 weeks in two public schools in São Paulo City. 24 children were randomly screened and distributed between control group and experimental group. C-TRF scale was used as the evaluation method. The outcomes have shown significant improvements in attention problems, external behavior as well as in the time spent in the activity. The essay also discusses factors which contributed to the practical methods results and the development of attention in pre-school age